1988
DOI: 10.1021/j100334a035
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite face surface associated tris(bipyridine)chromium(3+) monitored electrochemically

Abstract: possible to achieve the same fitting with those three parameters by a strictly numerical procedure (e.g., nonlinear least-squares fitting by successive Gaussian linearizations).The case of the Helmholtz layer capacitance (Figure 4d) as a fitting parameter is different. Large variations in that parameter cause only small distortions in the theoretical curve. Also, by comparison with the other Figure 4 and with eq 22, errors in that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 1 publication
3
30
0
Order By: Relevance
“…It will be first examined how the presence of Na-Sa and HDTMA-Sa films onto the electrode surface would influence its response to redox probes either positively or negatively charged. As expected, the two probes ([Ru(NH 3 ) 6 ] 3þ and [Fe(CN) 6 ] 3À ) gave rise to well defined reversible cyclic voltammograms at a bare glassy carbon electrode (Fig. 2).…”
Section: Physicochemical Characterization Of the Modifiedsupporting
confidence: 79%
See 2 more Smart Citations
“…It will be first examined how the presence of Na-Sa and HDTMA-Sa films onto the electrode surface would influence its response to redox probes either positively or negatively charged. As expected, the two probes ([Ru(NH 3 ) 6 ] 3þ and [Fe(CN) 6 ] 3À ) gave rise to well defined reversible cyclic voltammograms at a bare glassy carbon electrode (Fig. 2).…”
Section: Physicochemical Characterization Of the Modifiedsupporting
confidence: 79%
“…This work aims at providing useful information about the sorption processes of [Ru(NH 3 ) 6 ] 3þ and [Fe(CN) 6 ] 3À at a surfactant-intercalated clay modified electrode. This will be achieved via the utilization of multisweep cyclic voltammetry technique to investigate the effect of many parameters such as the ionic strength, the film surfactant loading and the pH of the supporting electrolyte, on the permeability and preconcentration behavior of the modified electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest signal is obtained by drying 1 pL of a 5 g/L suspension on the electrode. This results in a dry film thickness of 0.3 p m [9]. Increasing the thickness of the film causes a decrease in the maximum current observed.…”
Section: A) Ku(nhand+ Is Excluded From the Interlayer Regionmentioning
confidence: 99%
“…Although smectites are electrochemically inactive, it has been reported that the metal complexes adsorbed into a clay film are active electrochemically (Gosh & Bard, 1983). Since then, many reports have appeared on the application of clay-modified electrodes (Fitch, 1990;Fitch & Lee, 1993;Itaya & Bard, 1985;Ege et al, 1985;Lee & Fitch, 1990;Fitch et al 1988;Rong et al, 1990;Kaviratna & Pinnavaia, 1992;Gobi et al, 1994;Labbe et al, 1994;Fitch & Krzysik, 1994;Xiang & Villemure, 1994;Mousty et al, 1994;Shen et al, 1994). The detailed mechanisms at the electrodes, however, remain to be clarified.…”
mentioning
confidence: 99%